IMPROVEMENT OF TECHNOLOGY OF SEMI-FINISHED PRODUCTS FOR PIZZA WITH HIGH CONTENT OF DIETARY FIBERS - ANTONENKO Аrtem; BROVENKO, Tetiana; KRYVORUCHKO, Myroslav; STUKALSKA, Nataliya; TOLOK, Galina; TONKYKH, Oleksii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article presents the technology of semi-finished products from yeast dough for pizza with high content of dietary fiber. The expediency of using biologically active raw materials in the developed technology is substantiated. It is established that the use of apple pomace powder in the composition of semi-finished products for pizza more than 15% by weight of flour is impractical, as it significantly reduces the sensory quality of products. The use of apple pomace powder allows to increase the content of dietary fiber in the composition of semi-finished products from yeast dough for pizza by 9.7% compared to the control, which allows to meet the daily requirement for them at 22.9%. The chemical composition of pizza semi-finished products using apple pomace powder in some respects improved compared to control: the content of B vitamins increased by 58.33%, the amount of vitamin PP increased by 63.64%, the amount of manganese increased by 26.32%. The chemical composition of pizza with tomatoes and cheese using apple pomace powder in some respects improved compared to control: the content of B1 vitamins increased by 160%, the amount of vitamin PP increased by 60%, the amount of manganese increased by 4.53%. Satisfaction of daily requirement in dietary fiber at consumption of 100 g of the developed pizza increases from 4.0 to 23,7%, in potassium - from 3,71 to 9,63%, vitamin B1 - from 2,94 to 7,65%, vitamin B2 - from 4.0 to 8.0% compared to control. A comprehensive indicator of the quality of semi-finished pizza products using apple pomace powder, which is 2.6 units, which is 22.9%, exceeds the control value (0.5 units). The social effect of the introduction of the developed semi-finished product from yeast dough for pizza with high dietary fiber content is to expand the range of meals for adults and children with high content of essential nutrients, improved consumer properties, which will help protect the health of the population. environment. Developed culinary products can be recommended for nutrition in the daily diets of people working in heavy industry, living in environmentally contaminated areas and all segments of the population.